Manipulating Gibberellin Control Over Growth and Fertility as a Possible Target for Managing Wild Radish Weed Populations in Cropping Systems - Groszmann, Michael; Chandler, Peter M.; Ross, John J.; Swain, Steve M. (Frontiers in Plant Science, 2020)
Wild radish (Raphanus raphanistrum) is a major weed of Australian cereal crops. A rapid establishment, fast growth rate and abundant seed production are fundamental to its success as an invasive species. Wild radish has also developed resistance to a number of commonly used herbicides increasing the problem. New innovative approaches are needed to control wild radish weed populations. Here we explore the possibility of pursuing gibberellin (GA) biosynthesis as a novel molecular target for controlling wild radish, and in doing so provide new insights into GA biology. By characterizing ga3ox mutants in Arabidopsis, a close taxonomic relative to wild radish, we showed that even mild GA deficiencies cause considerable reductions in growth and fecundity. This includes an explicit requirement for GA biosynthesis in successful female fertility. Similar defects were reproducible in wild radish via chemical inhibition of GA biosynthesis, confirming GA action as a possible new target for controlling wild radish populations. Two possible targeting approaches are considered; the first would involve developing a species-specific inhibitor that selectively inhibits GA production in wild radish over cereal crops. The second approach involves making crop species insensitive to GA inhibitors, allowing the use of existing broad spectrum GA inhibitors to control wild radish populations. Towards the first concept, we cloned and characterized two wild radish GA 3-OXIDASE genes, identifying protein differences that may allow for selective inhibition of dicot over monocot GA3-OX activity. We developed a yeast based system to assay GA3-OX activity that could be used for screening of inhibitory compounds. For the second approach, we demonstrated that a subset of GA associated sln/rht overgrowth mutants, recently generated in cereals, are insensitive to GA reductions brought on by the general GA biosynthesis inhibitor, paclobutrazol. The location of these mutations within sln/rht, provides new insight into the functional domains of these important GA signaling proteins. It would appear that targeting the GA pathway could be a viable inclusion in management programs combating wild radish. In drawing this conclusion, we provided new insights into GA regulated reproductive development and molecular characteristics of GA metabolic and signaling proteins.